Design of Realistic Mathematics Education-Based Student Worksheets to Improve Students' Mathematical Problem-Solving Skills - Anggita Manggarrani; Nafida Hetty Marhaeni; Ageng Triyono (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This study focuses on the design and development of student worksheets based on Realistic Mathematics Education (RME) principles aimed at enhancing students' mathematical problem-solving skills. The research adopts a design-based research methodology, involving iterative cycles of design, implementation, analysis, and refinement. The RME approach emphasizes the use of real-world contexts to facilitate meaningful learning and engagement with mathematical concepts. The designed worksheets integrate realistic scenarios, encouraging students to apply mathematical reasoning in practical situations. Preliminary testing with a sample group of middle school students indicates significant improvements in their problem-solving abilities, as evidenced by increased performance in solving complex mathematical tasks. The results suggest that RME-based worksheets are effective tools for promoting deeper understanding and practical application of mathematics. Future work will involve larger-scale testing and further refinement of the worksheets to ensure their efficacy and adaptability across diverse educational settings.